Silsesquioxanes as nanofillers. Part I. Silicone matrix nanocomposites - Maciejewski, H.; Dutkiewicz, M.; Byczyński, Ł.; Marciniec, B. (Polimery, 2012)
The paper is the first of a series of review articles on the use of polysilsesquioxanes (POSS) for the modification of various polymers in order to prepare nanocomposites with specific physico-chemical properties. It has been the aim of the authors, in this and the following parts, to present the current state of knowledge and directions for further investigation in this area of chemistry. This opening paper reports on the synthesis, properties and use of nanocomposites based on POSS and silicone matrix.